Just Mercy: Theo-Ethical Reflections for Practicing Care in Carceral and Other Death-Dealing Spaces - Green, Rachelle (Journal of pastoral theology, 2025)
Grounded in empirical insights from qualitative prison research, this essay presents first-hand narratives of two women surviving incarceration whose stories reveal what I contend are liberating demonstrations of mercy. Viewed alongside the womanist theological contributions of Kelly Brown Douglas and the feminist theo-ethical contributions of Cara Curtis, these stories offer a model of mercy as an embodied practice that provides sanctuary for bodies in need, generates delight, and seeks to leave no one behind. This image of genuine mercy starkly contrasts the ‘no mercy’ practiced by carceral institutions that breeds injustice and diminishes quality of life for those constrained by its domination.